ENGLISH LANGUAGE TEACHING AND LEARNING FOR AUTISTIC STUDENTS - Wulandari, Anik (ENCOUNTER, 2012)
Teaching autistic students is not as easy as teaching normal students. The teacher needs more patience and various creativities. This study is aimed to investigate the English Language Teaching Learning for autistic students at the eighth grade of SMPLB Negeri Semarang in terms the English teaching material, teaching method, and learning assessment. This study uses qualitative approach because the data are described in written and spoken form. The data were collected by three techniques; observation, interview, and documentation. This research focused on teaching materials which consist of teaching materials, textbooks, and teaching sources; teaching methods with particular reference on the teaching method and teaching media; and learning assessments which cover the technique of learning assessment and feedback. The result of this study showed that the curriculum used in English language teaching and learning process at eighth grade of SMPLB Negeri Semarang is PPI (Proses Pembelajaran Individu/Individual Learning Process) curriculum. There have been certain syllabus and Lesson Plan arranged in the previous year. Language materials and topics covered in English course for autistic students at eighth grade are arranged based on PPI curriculum which consist of three themes for each semester. Several teaching and learning methods are Audio Lingual Method, Total Physical Response, and Direct Method. The English learning assessment is very limited which forms oral test and written test. The oral tests include the stimulating questions while written tests forms multiple choice type and short answer task.